Europe’s responsibility to protect: from Kosovo to Syria - Gottwald, Marlene (The University of Edinburgh, 2014)
With lessons learned from the 1999 Kosovo intervention as a point of departure, this thesis addresses the question of whether the development of the Responsibility to Protect (RtoP) doctrine and the Common Security and Defence Policy (CSDP) actually made a difference in determining whether and how Europe responded to subsequent mass atrocities in its neighbourhood. Viewing the RtoP as an emerging international norm, a social constructivist framework is applied to explore the influence of norms on European foreign policy-making. It is argued that even an emerging international norm can be influential if it is considered a legitimate behavioural claim. The influence of the RtoP will be assessed by gauging the extent to which it is distinctively used to justify foreign policy decisions and to communicate the basis for those choices to a wider audience. The development of the RtoP and the CSDP from 1999-2011 in theory and practice paves the way for an in-depth case study analysis. Focusing on the UN, the EU as well as French, German and British discourses, the question of whether the RtoP has actually made a difference will be answered by scrutinizing European responses to the Libyan crisis (March – October 2011) and the Syrian crisis (March 2011 – September 2013). Ultimately, light is shed not only on the relevance of the RtoP for Europe but also on the role of the EU as a security actor in its neighbourhood.
Keywords: European foreign policy; European Union; responsibility to protect; human security; Kosovo; Syria; Libya